Development of semi-automatic solar gate system (Mechanical Part) - Shashi Kumar, S A Karagaratnan (2008)
This thesis deals with the development of semi-automatic solar gate system (mechanical part). The objectives of this thesis are to design the mechanical part of gate system, fabricate the parts and assemble the parts together to complete the semi-automatic solar gate system. The thesis describes the methods of designing and fabricating the mechanical part of the gate system. There the many steps taken to design and fabricate the mechanical part of the gate system. The structural three-dimensional solid modelling of gate system was developed by using the SolidWorks engineering drawing software. The fabrication process also undergoes many steps such as material marking, cutting, drilling, welding, grinding and finalizing the gate system by painting. Other than that, it is explaining the procedure of testing where the mechanical part integrated with controller part to operate the mechanism of semi-automatic solar gate system. The results of testing the prototype also discussed in this thesis. Finally, the conclusion about this project and the recommendations for the future plan also attached together with this thesis.